Peripheral blood and hemoglobin electrophoresis pattern in beta thalassemia major patients receiving repeated blood transfusion (Faculty of Medicine Universitas Indonesia, 2004)
One hundred and fifteen beta thalassemia major outpatients attending the Thalassemia Center Department of Child Health, Medical School University of Indonesia Dr. Cipto Mangunkusumo General Hospital for routine blood transfusion and hematology examination, participated in this study. There was a negative correlation between the size of the spleen and the peripheral blood parameters. All peripheral blood parameters tend to decrease with the enlargement of the spleen, and the condition is reversed after splenectomy. We observed that hypersplenism starts when the spleen is as big as S (V – VI). The hemoglobin electrophoresis pattern from beta thalassemia major patients receiving repeated blood transfusion did not show a dense HbF fraction, 90 patients showed a normal hemoglobin electrophoresis pattern. A hemoglobin analysis of both parents could be useful to confirm the diagnosis of beta thalassemia major for patients receiving repeated blood transfusion. In order to get a definite diagnosis, a genetic analysis by bio molecular technique is needed. (Med J Indones 2004; 13: 8-16) Keywords: β thalassemia major, hematology parameter, hemoglobin electrophoresis